On the Convergence of Bernstein-Stancu Polynomials in the Variation Seminorm. (2nd February 2016) - Öksüzer, Özlem; Karsli, Harun; Yeşildal, Fatma Taşdelen
ABSTRACT: This article studies the variation detracting property and rate of approximation of the Bernstein-Stancu polynomials in the space of functions of bounded variation with respect to the variation seminorm. Moreover, we will present Voronovskaya-type theorems for Bernstein-Stancu polynomials B n, α, β f and for the first derivative of these polynomials. Finally we include some graphical examples.